Pergeseran Peran OHD Dalam Dunia Seni Rupa Indonesia (Kajian Sosio Budaya) - Djaka S, Teguh (Institut Seni Indoensia Surakarta, 2009)
For perpetrators of art in Indonesia, the name of Oei Hong Jien (OHD) is not a foreign name. Born of a family who loves painting, OHD become the world's top collector of Indonesian art. He is now not only become another collector's reference (and abroad) who want to buy works of painter Indonesia, but also a member of the Board of Directors and the Singapore Art Museum Singapore Art Retreat. Especially after OHD build an art museum containing paintings collection, adding to the prestige OHD as a collector and curator of the higher. From several sources obtained by the author, now at least OHD has collected 1500 painting, from a variety of visual styles and generations. From the works of old masters such as Affandi, Sudjoyono, Hendra Gunawan, Entang Wiharso, Adi Yuswantoro novice painter to emerge to the surface. Given all these facts, make a referral OHD museum and research data sources Indonesian art development for researchers from Indonesia and Overseas. This phenomenon is written in this article, which is related to (1) Background OHD so loved the painting until he wants to collect more than 1000 paintings. (2) There is a shift in the role of OHD in the Indonesian art world, from the limited apresian / consumers (collectors) to be a gallery curator and advisor and board member and Director of the Singapore Art Museum Singapore Art Retreat with authority or power to determine the value of a work or artist. (3) The background of thought or interest of OHD and when he prefers not to establish a museum gallery/ showroom collection. Key words: OHD, collectors, curators